PERBANDINGAN MODEL PEMBELAJARAN THINK TALK WRITE (TTW) DENGAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS XI SMA N I GUNUNG TULEH - Lola Lola (Horizon, 2021)
This research is motivated by the problem of students not being skilled in writing explanatory text. This study aims to describe the Comparison of Think Talk Write (TTW) Learning with Scramble Explanatory Text Skills of Class XI Students of SMA N I Gunung Tuleh. This type of quantitative research with experimental. The research sample was 50 students of class XI SMAN I Gunung Tuleh consisting of 24 students/experiment I and 26 students/experiment II. The data of this study were the scores of explanatory text writing skills using the Think Talk Write (TTW) Scramble model of class XI students of SMA N I GunungTuleh. The risearch results can be sumarized as follows. First, the explanatory text writing skills of class XI SMA N I Gunung Tuleh with the Think Talk Write (TTW) model obtained an average of 63.33 in the range of 56-65% with sufficient qualifications (C). Second, the students' explanatory text writing skills ofclass XI SMA N I Gunung Tuleh with the Scramble model obtained an average of 70.76 in the range with the qualification More than Enough (LdC). Third, based on the t-test of the hypothesis tcount>ttable (2.33> 1.67). So it can be concluded that the use of the Scramble model is better used to improve the explanatory text writing skills of class XI students of SMA N I Gunung Tuleh. Third, based results of the t-test there is a comparison of the use (TTW) with the Scramble model on the explanatory text writing skills of class XI SMA N I Gunung Tuleh because tcount>ttable (2.33>1.67). So, it can be concluded that the use of the Scramble model is better used to improve the explanatory text writing skills of class XI SMA N I Gunung Tuleh.